Manajemen Mutu Kinerja Dosen Politeknik Kesehatan - Syarief, Osman (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2013)
The Quality Management of the Lecturers' Performance in the Polytechnic of Health Sciences (An Analysis of the Influence of Leadership Behavior, Organizational Climate, Achievement Motivation and Commitment on the the Lecturers' Performance in the Polytecnic of Health Sciences Ministry of Public Health in Bandung). The low competency of the Polytecnic of Health Sciences graduates in Indonesia is currently under the spotlight. This phenomenon is assumed to have a significant correlation with the achievement of the Human Development Index target. Based on the theoretical review, the low competency of the graduates is caused by the low performance of the lecturers. From the theoretical point of view, the low performance of the lecturers can be influenced by the lecttirers motivation, commitment, leadership and organizational climate. Based on this framework, the writer is interested to conduct the quantitative research through survey method. This research is carried out in the Polytecnic of Health Sciences in Bandung. The population of the research is 268 lecturers, and the sample is determined by Cochran theory (2009) and resulted in 161 lecturers as the sample. The respondents of this reseach are lecturers and students. Path analysis is used as the tehnique of analysis. The result of the research shows that the average score of the quality of the lecturer’s performance in the Polytecnic of Health Sciences is in average category. The aspect of teaching and learning process is more dominant compared to the performance of the research and community services aspects. This finding confirms the current practice of the lecturers who still prioritize teaching and learning, rather than the research and community service activities. The variables of achievement motivation, lecturers' commitment, leadership behavior, and organizational climate variables influence the lecturers' performance both simultaniously and individually. It means that the lecturers' performance is influenced by achievement motivation, lecturers' commitment, leadership behavior, and organizational climate variables. Among the four variables, the achievement motivation has the strongest influence on the lecturers' performance. This research offers an alternative hyphotetic strategy for managing the improvement of lecturers' performance which can be used by the leaders of the Polytecnic of Health Sciences as the input material to improve the quality of human resources, especially lecturers.